2011
DOI: 10.5339/avi.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cultural and social factors on healthy lifestyle of Arabic women

Abstract: Cardiovascular diseases are the leading cause of mortality and morbidity globally. Similar to other Western and Gulf countries, the incidence of cardiovascular disease and coronary artery diseases such as acute myocardial infarction is rising rapidly in Qatar. Diabetes mellitus, smoking, and hypertension are the most common risk factors causing acute myocardial infarction, congestive heart failure, and stroke. Additionally, obesity resulting from physical inactivity and unhealthy diet can lead to metabolic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…Similar to the findings of previous studies conducted in the EMR [ 23 32 ], barriers to participants’ PA are: the presence of disease(s), feeling tired and pain, lack of willpower and motivation, lack of time and energy to exercise, low personal priority of health and competing demands, cultural norms and practices of public modesty (i.e., the need for women to wear traditional dress and to be accompanied by a male family member when going out), lack of social support, friends and companionship, low value of exercise such as insufficient health discourse in daily life, lack of affordable and accessible environments to exercise, lack of information about PA, and lack of supportive social milieu for PA especially for women. Congruent with the previous studies [ 25 , 26 , 31 , 33 ], participants of this study suggested that the motivation to “fight” disease(s)/illnesses, perceived benefits of PA, having willpower and motivations to be fit, have fun and good health, being religious, valuing individual responsibility for health, having supportive social systems and affordable and accessible exercise facilities were facilitators to be physically active. The findings of this study add to the existing evidence that PA is a contextualized experience within the specific society, culture, and history.…”
Section: Discussion and Recommendationscontrasting
confidence: 49%
See 3 more Smart Citations
“…Similar to the findings of previous studies conducted in the EMR [ 23 32 ], barriers to participants’ PA are: the presence of disease(s), feeling tired and pain, lack of willpower and motivation, lack of time and energy to exercise, low personal priority of health and competing demands, cultural norms and practices of public modesty (i.e., the need for women to wear traditional dress and to be accompanied by a male family member when going out), lack of social support, friends and companionship, low value of exercise such as insufficient health discourse in daily life, lack of affordable and accessible environments to exercise, lack of information about PA, and lack of supportive social milieu for PA especially for women. Congruent with the previous studies [ 25 , 26 , 31 , 33 ], participants of this study suggested that the motivation to “fight” disease(s)/illnesses, perceived benefits of PA, having willpower and motivations to be fit, have fun and good health, being religious, valuing individual responsibility for health, having supportive social systems and affordable and accessible exercise facilities were facilitators to be physically active. The findings of this study add to the existing evidence that PA is a contextualized experience within the specific society, culture, and history.…”
Section: Discussion and Recommendationscontrasting
confidence: 49%
“…At an individual level, lack of time to exercise, lack of willpower, the presence of health conditions, fatigue/tiredness, ruining grooming efforts such as clothing and make-up for women, and lack of experience with exercise were reported as hindering physical activity [ 23 26 ]. At a sociocultural level, cultural and social norms such as women need to be accompanied by a male family member when going outdoors, public modesty, and the need to wear traditional dress, women’s roles and domestic responsibilities, social milieu that deemphasizes the importance of PA, lack of health discourse in society, and social belief and attitude towards women who try to be physically active, were reported as barriers [ 23 , 25 , 27 30 ]. At an organizational and political level, allocation of funding for sports, especially for women, i.e., limited access and funding for women to join exercise facilities such as sports clubs, jogging trails, swilling pools, lack of information on exercise, costs of gym memberships, and living in suburban or villages where there are less funding for sports programs were reported as barriers [ 25 , 28 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is strong evidence of the benefits of HD in primary prevention of major cardiovascular events and reducing the risk of diabetes among people with high cardiovascular risk. 42 43 In a recent qualitative study, Donnelly and colleagues 28 examined sociocultural factors that influenced the healthy lifestyles (ie, diet, PA, non-smoking) of 50 Arabic women with heart diseases living in Qatar. The participants reported that their diets tended to be high in salt, sugar and fats.…”
Section: Discussionmentioning
confidence: 99%